Genremönster i 'Ministern har ordet'. Regeringar rapporterar om bolag med statligt ägande - Enell-Nilsson, Mona; Rahm, Henrik (My University, 2021)
The article deals with the genre consolidated government accounts of state-owned enterprises in Finland and Sweden. More specifically, the study is focused on the subgenre the foreword of the responsible minister, which we label Statement from the Minister in analogy with Statement from the CEO in the related genre corporate annual reports. The primary data consist of Statement from the Minister in Finland and Sweden 2007–2016, thus 20 texts. The main point of departure is a genre analysis based on rhetorical moves and steps in Statement from the CEO (Skulstad 1996, 2002). The three moves are Establishing relationships, Maintaining confidence and Reinforcing the relationships. The analysis shows that the three moves and most of the steps are used in both countries. The differences are found in the realisations where strategies, expectations of future and reassurance are expressed as much in political terms as in economic terms in the analysed data. In the Swedish data, sustainability is prioritized during the whole period and connected to the political ambition to be a real model. The subgenre has found its form and content in Sweden since it exists in the present format since 1999. In the Finnish data, the variation is wider as the subgenre was introduced as late as 2007. Since it was taken out of use due to a change of the reporting format in 2017, it did not get the chance to institutionalise as a subgenre to consolidated government accounts.
Keywords: genremönster; retoriska drag; retoriska steg; statligt ägda bolag; fi=Markkinointi|en=Marketing|